NON-PERFORMING LOANS - Xalimova Nilufar Umidjon qizi (Journals Park Publishing, 2024)
Problem loans are important in ensuring the development of the banking system and the economy. This article analyzes the causes of the emergence of problems, the impact of credit on the banking sector and the economy, national problems, methods of managing and correcting problem loans. Problem loans can be associated with various economic, economic instability, weak management, and monitoring. The article, loans and work, conducted in Uzbekistan on the world scale on problematic and received from them.
Keywords: Bank, loan, borrower, overdue debt, problematic loan, NPL, loan monitoring, risk of non-repayment of the loan.